INVERSE PROBLEM FOR WAVE EQUATION WITH DIRICHLET BOUNDARY CONDITION - Ahmad, Sofwah
This thesis discusses monochromatic inverse problem on reconstructing potential function q(x) from single frequency(or spectral data), of the wave equation with Dirichlet boundary conditions. The reconstruction approach used in this thesis is by applying the method of separation of variables and transforming the obtained eigenvalue problem into integral equation using the method of variation of parameters. The relationship between potential function q(x) and the spectral data(RUMUS) are obtained from the generated integral equation. The reconstruction is done numerically, applying the regularization algorithm to the linear system on Rn. The background theory of inverse problem is also given.